1988
DOI: 10.1152/jn.1988.60.5.1765
|View full text |Cite
|
Sign up to set email alerts
|

Response of vestibular neurons to head rotations in vertical planes. II. Response to neck stimulation and vestibular-neck interaction

Abstract: 1. We have studied the responses of neurons in the lateral and descending vestibular nuclei of decerebrate cats to stimulation of neck receptors, produced by rotating the body in vertical planes with the head stationary. The responses to such neck stimulation were compared with the responses to vestibular stimulation produced by whole-body tilt, described in the preceding paper. 2. After determining the optimal vertical plane of neck rotation (response vector orientation), the dynamics of the neck response wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 0 publications
6
27
0
Order By: Relevance
“…In this way, VO neurons and PVP neurons in rhesus monkeys are comparable after lesion (compare with Sadeghi et al 2010). Similar findings have been reported in studies performed in the vestibular nuclei of normal cats (Kasper et al 1988), squirrel monkeys (Gdowski et al 2001), and cynomolgus monkeys (Sadeghi et al 2009). …”
Section: Functional Role For Unmasking Of Neck Proprioceptive Signalssupporting
confidence: 88%
See 1 more Smart Citation
“…In this way, VO neurons and PVP neurons in rhesus monkeys are comparable after lesion (compare with Sadeghi et al 2010). Similar findings have been reported in studies performed in the vestibular nuclei of normal cats (Kasper et al 1988), squirrel monkeys (Gdowski et al 2001), and cynomolgus monkeys (Sadeghi et al 2009). …”
Section: Functional Role For Unmasking Of Neck Proprioceptive Signalssupporting
confidence: 88%
“…As such, VO neurons are similar to VOR interneurons (i.e., PVP neurons) in that neck inputs are unmasked only after lesion (Sadeghi et al 2010). Interestingly, in both studies, the percentage of neck-sensitive neurons observed after lesion (ϳ50%) was comparable to that observed in normal conditions in other species (Gdowski et al 2001;Kasper et al 1988;Sadeghi et al 2009). We suggest that the acute appearance of neck proprioceptive signals in the vestibular nuclei neurons of rhesus monkeys after lesion reveals neck-vestibular connections that are present before lesion, but make silent synapses on vestibular nuclei neurons that become active only when vestibular inputs are decreased.…”
Section: Unmasking Of Neck Proprioceptive Signalssupporting
confidence: 80%
“…Forty-two percent of the cells also responded to angular rotation about an earth-vertical axis (n ϭ 65). Similar patterns of angular and linear convergence have been reported previously in cat vestibular nucleus (Baker et al 1984;Iwamoto et al 1996;Kasper et al 1988), rat vestibular nucleus , monkey vestibular nucleus (Chen-Huang and McCrea 1999;Dickman and Angelaki 2002;Tomlinson et al 1996), and monkey fastigial nucleus (Büttner et al 1999;Shaikh et al 2005a;Siebold et al 1997Siebold et al , 1999Zhou et al 2001). …”
Section: R E S U L T Ssupporting
confidence: 80%
“…The interaction between vestibular and joint afferents already occurs at the level of the vestibular nuclei, the first central synapse of primary vestibular afferents (Boyle and Pompeiano, 1981;Anastasopoulos and Mergner, 1982;Wilson et al, 1990). Many VN neurons respond to both vestibular and proprioceptive stimulation (Brink et al, 1980;Kasper et al, 1988). Given such extensive vestibular-proprioceptive convergence in the VN and the fact that the paramedian zone of the anterior vermis projects directly to the lateral vestibular nucleus (Voogd, 1989), the observation that the VN cell population described here used a motion reference frame that was not body-fixed might appear surprising.…”
Section: Vestibular-somatosensory Convergencementioning
confidence: 99%